Gereja Santo Antonius Purbayan: Sejarah Awal Gereja Katolik Belanda di Solo - Ahmad Yunani (Jurnal Lektur Keagamaan, 2016)
The Catholic Church Santo Antonius Purbayan be evidence of history in the development and spread of Catholicism in Solo or Surakarta. This article attempts to examine the role of the church as the center spread of Catholicism in Solo and its surroundings, from the activities of the church became a place of worship, even to the historical development of Catholic educational institutions are quite old. This study uses Arkheologis Historical approach that is supported by the data history of the church in question. And in the findings of this study, it was found that the existence of this church to witness the historical presence of the Catholic religion in Solo, and some other areas in Java. Spread starts from Semarang by a Catholic priest is Father Van Lith, SJ. When coming in Java, he learned a few things that made the failure of the missionaries before. They came as a waitress Faith to Dutch society that has been present with different purposes and objectives. The Church was built by the Dutch in the form of Neo Gothic, to conform and adapt to the cultural conditions that developed at that time. In its development, to support its existence, the church establish educational institutions that cater for the Catechist who trained as priests and Catholic Faith waitress in Solo and its surroundings. Keywords: Church of Santo Antonius Purbayan, Solo, Catholicism, Architecture Gereja Katolik Santo Antonius Purbayan menjadi bukti sejarah dalam perkembangan dan penyebaran agama Katolik di Solo atau Surakarta. Artikel ini mencoba mengkaji peran gereja sebagai pusat penyebaran Agama Katolik di Solo dan sekitarnya, dari aktifitas gereja yang menjadi tempat ibadah, bahkan hingga sejarah berkembangnya lembaga pendidikan Katolik yang cukup tua. Penelitian ini menggunakan pendekatan Historis Arkheologis yang didukung dengan data sejarah gereja dimaksud. Dan dalam temuan penelitian kali ini, ditemukan bahwa keberadaan gereja ini menjadi saksi sejarah hadirnya agama Katolik di Solo, dan beberapa daerah lainnya di tanah Jawa. Penyebarannya dimulai dari kota Semarang oleh seorang Imam Katolik yaitu Romo Van Lith, SJ. Saat datang di tanah Jawa, ia mempelajari beberapa hal yang menjadikan kegagalan para missionaris sebelumnya. Mereka datang sebagai Pelayan Iman bagi masyarakat Belanda yang telah hadir sebelumnya dengan berbagai maksud dan tujuan. Gereja dibangun oleh Belanda dengan bentuk Neo Gothik, dengan mengikuti dan menyesuaikan dengan kondisi budaya yang berkembang saat itu. Dalam perkembangannya, untuk mendukung keberadaannya, pihak gereja membentuk lembaga pendidikan yang diperuntukkan bagi para Katekis yang dididik menjadi Imam dan Pelayan Iman Katolik di Solo dan sekitarnya. Kata kunci: Gereja Santo Antonius Purbayan, Solo, Katolik, Arsitektur